Can Argument-Driven Inquiry-Assisted Virtual Laboratory Improve Pre-service Physics Teachers' Mastery Concept of Simple Harmonic Oscillation? - Karawahenni, Yolanda Dwi Vivian; Sutopo, Sutopo; Hidayat, Arif; Mustika, Maya (Jurnal Pendidikan Sains, 2024)
This study endeavors to ascertain the efficacy of the Argument-Driven Inquiry (ADI)-assisted virtual laboratory learning model in enhancing the comprehension of simple harmonic oscillation concepts among pre-service physics teachers. Employing a mixed-method approach with an embedded experimental design, the investigation employs a reasoned multiple-choice instrument comprising 15 questions. Analysis of the results reveals a noteworthy 48.38% increase in the average mastery of concepts between the pre-test and post-test, yielding an N-gain value of 0.63. Statistical scrutiny through paired sample t-tests corroborates significant disparities between pre-test and post-test scores, evidenced by a tcount (16.28) exceeding the critical ttable value (1.69) with a two-tailed significance value of 0.00. Furthermore, effect size analysis underscores the substantial impact of the ADI-assisted virtual laboratory learning model on augmenting students’ conceptual mastery. This underscores the viability of employing the ADI-assisted virtual laboratory learning model to enhance pre-service physics teachers’ understanding of simple harmonic oscillation concepts. However, refinement of the ADI syntax is recommended, particularly by substituting the report writing session with a learning reflection activity, without compromising the essence of ADI as an inquiry-based, argumentative learning model. It is anticipated that the outcomes of this study will influence the advancement of learning models in Indonesia, particularly the ADI paradigm. DOI: 10.17977/jps.v12i12024p023